1977
DOI: 10.1001/archneur.1977.00500180021004
|View full text |Cite
|
Sign up to set email alerts
|

The Third Alexia

Abstract: A variety of alexia has been demonstrated that can be distinguished from the two classically recognized types of alexia. This reading disorder is seen in patients with a dominant frontal lobe pathologic condition that has produced a motor language disturbance (Broca aphasia) and is sufficiently disabling to deserve consideration as a variety of alexia. Functionally, the frontal reading disturbance differs from the other two types in that the patient comprehends meaningful content words better than relational o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

1981
1981
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(20 citation statements)
references
References 12 publications
(1 reference statement)
1
15
0
4
Order By: Relevance
“…Paulesu et al (16) have reported underactivation in the insula in dyslexia, but Rumsey (17) and we find no support for this claim. Our findings implicating the IFG in developmental dyslexia are consonant with reports of acquired alexia accompanying some aphasias of the Broca type that have also involved this anterior region (37).…”
Section: Discussionsupporting
confidence: 91%
“…Paulesu et al (16) have reported underactivation in the insula in dyslexia, but Rumsey (17) and we find no support for this claim. Our findings implicating the IFG in developmental dyslexia are consonant with reports of acquired alexia accompanying some aphasias of the Broca type that have also involved this anterior region (37).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we note that the left dorsolateral frontal lesion in Anderson et al's (1990) patient is not in a location we would ordinarily expect to produce impaired letter identification, although other reading impairments are sometimes associated with lesions in this general area (e.g., Benson, 1977;Berndt 8c Caramazza, 1980). In Starrfelt's (2007) case, the lesion locus was not identified.…”
Section: Discussionmentioning
confidence: 68%
“…24). Interestingly, there have been suggestions that at least some Broca's aphasics do exhibit a reading impairment, with one distinguishing feature being the relative inability to read single letters as compared with words (27)(28)(29). Unfortunately, neurological case descriptions of such Broca's aphasics have not systematically included measures of both word and nonword reading accuracy, and in some cases reading skills were assessed by using a measure of comprehension rather than pronunciation (e.g., point to the picture that matches a written word; ref.…”
Section: The Left Frontal Cortex and Phonological Dyslexiamentioning
confidence: 99%